KERANGKA PEMIKIRAN PROYEK PENGEMBANGAN SISTEM KEWASPADAAN PANGAN DAN GIZI DI INDONESIA - Darwin Karyadi; Ignatius Tarwotjo; Djumadias Abunain; J-P Habicht; R.M. Brooks; David O.Dapice (Persagi, 1984)
-